NOVEL APPROACH TO MANAGEMENT OF SECONDARY BRONCHIOLITIS OBLITERANS ORGANIZING PNEUMONIA FOLLOWING INFLUENZA A - Madegedara, Dushantha; Nawarathne, Ishelda; Basnayake, Lihini; Luckmy, S. A.; Imbulpitiya, B (International Journal of Research -GRANTHAALAYAH, 2020)
A 50-year old man presented with a short history of fever, pleuritic type chest pain followed by progressively worsening dyspnea and hypoxemic respiratory failure. Influenza A virus antigen was identified from a throat swab. Mechanical ventilation and oseltamivir therapy were commenced, but was associated with an unfavorable response. High-resolution computed tomography (HRCT) of chest revealed features of Bronchiolitis Obliterans Organizing Pneumonia (BOOP). Here we report the 1st case of steroid resistant BOOP secondary to influenza A infection which subsequently responded well to Cyclophosphamide therapy.